A New Variant of B-Spline for the Solution of Modified Fractional Anomalous Subdiffusion Equation. (5th July 2021) - Hashmi, M. S.; Shehzad, Zainab; Ashraf, Asifa; Zhang, Zhiyue; Lv, Yu-Pei; Ghaffar, Abdul; Inc, Mustafa; Aly, Ayman A.
Abstract : The objective of this paper is to present an efficient numerical technique for solving time fractional modified anomalous subdiffusion equation. Anomalous diffusion equation has its role in various branches of biological sciences. B-spline is a piecewise function to draw curves and surfaces, which maintain its degree of smoothness at the connecting points. B-spline provides an active process of approximation to the limit curve. In current attempt, B-spline curve is used to approximate the solution curve of time fractional modified anomalous subdiffusion equation. The process is kept simple involving collocation procedure to the data points. The time fractional derivative is approximated with the discretized form of the Riemann-Liouville derivative. The process results in the form of system of algebraic equations, which is solved using a variant of Thomas algorithm. In order to ensure the convergence of the procedure, a valid method named Von Neumann stability analysis is attempted. The graphical and tabular display of results for the illustrated examples is presented, which stamped the efficiency of the proposed algorithm.